The who, what, and how of virtual participation in environmental research - Jennifer M. Holzer; Julia Baird; Gordon M. Hickey (Socio-Ecological Practice Research, 2023)
As a group of social scientists supporting a large, national, multi-site project dedicated to studying ecosystem services in natural resource production landscapes, we were tasked with co-hosting kick-off workshops at multiple locations. When, due to project design and the Covid-19 pandemic, we were forced to reshape our plans for these workshops and hold them online, we ended up changing our objectives. This redesign resulted in a new focus for our team—on the process of stakeholder and rightsholder engagement in environmental and sustainability research rather than the content of the workshops. Drawing on participant observation, surveys, and our professional experience, this perspective highlights lessons learned about organizing virtual stakeholder workshops to support landscape governance research and practice. We note that procedures followed for initiating stakeholder and rightsholder recruitment and engagement depend on the convenors’ goals, although when multiple research teams are involved, the goals need to be negotiated. Further, more important than the robustness of engagement strategies is flexibility, feasibility, managing expectations—and keeping things simple.